Research Progress of Cut-Resistant Textile Materials - Zhai, Yanru; Mao, Lizhou; Shen, Yue; Yan, Xuefeng (Frontiers in Chemistry, 2021)
This article describes the physical properties, application fields and modification technologies of several commonly used cut-resistant textile raw materials and coating materials, and summarizes and compares and analyzes the current commonly used cut-resistant textile materials evaluation standards: EN420, EN388, ASTM F-1790, ISO13997. Finally, it is pointed out that lightness, softness and comfort are the future research and development directions of cut-resistant textiles. The article provides a preliminary reference for the application and modification of high-performance fibers and coating materials in cut-resistant textiles.